Tax reform for human development in Central America - Manuel R. Agosin; Alberto Barreix; Juan Carlos Gómez Sabaíni; Roberto Machado (CEPAL Review, 2005)
Tax revenue in Central American countries accounts for just 13.5% of their gross domestic product; and the resultant resource shortage means insufficient and low-quality public expenditure, and chronic fiscal deficits financed through borrowing. In 2003 interest payments absorbed an average of 18% of the subregion’s total tax revenue. In these open economies, whose enterprises need to become more internationally competitive, fiscal policy is crucial both for financing the necessary physical and social infrastructure and for combating the poverty that still afflicts roughly 40% of the population. The economic development of Central America therefore needs second-generation reforms to modernize its tax systems, in order to increase revenue by about four percentage points of GDP.